Physiotherapy Intervention in Children with Autism Spectrum Disorder : Case Report - Putri Satriani Agustina; Taufik Eko Susilo; Ratna Aziami Yustisia (Prosiding University Research Colloquium, 2022)
Autism Spectrum Disorder is a neurological disorder characterized by limited social communication and repetitive patterns of behavior, interests and activities. Children with autism spectrum disorder also have limitations in motor skills, coordination, balance, movement planning and movement control, as well as errors in processing information. to stimuli through touch or tactile. In this case, the MAW patient was diagnosed with Autism Spectrum Disorder with complaints that the child likes to throw things, limitations in communicating, always repeating words, excessive emotions, and likes to walk around in circles and there are some primitive reflexes that have not been integrated. MAW patients are given physiotherapy intervention with Neurosensorimotor Reflex Integration, Massage, and Physical Exercises to stimulate sensory, integrate reflexes, relax, tactile stimulation and improve motor skills. After being given the intervention 4 times, from T0-T4 the plantar reflexes were not integrated, from T0-T4 the Babynsky reflexes were not integrated, while the protective reflexes were integrated in T4. Children feel calmer receiving massage on T3 and T4. While the physical exercise intervention has not given significant results on motor improvement. There has been no significant change in children with autism spectrum disorders after giving physiotherapy intervention, which could be due to the lack of intensity and frequency of therapy.